Adjunctive Treatment With Avacopan, an Oral C5a Receptor Inhibitor, in Patients With Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 11 (31st October 2020) - Merkel, Peter A.; Niles, John; Jimenez, Richard; Spiera, Robert F.; Rovin, Brad H.; Bomback, Andrew; Pagnoux, Christian; Potarca, Antonia; Schall, Thomas J.; Bekker, Pirow; ,
Abstract : Objective: This study aimed to evaluate the safety of avacopan, an orally administered C5a receptor inhibitor, for the treatment of antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis in addition to standard‐of‐care (SOC) treatment with glucocorticoids with cyclophosphamide or rituximab. Methods: In this randomized 12‐week study, twice daily avacopan (10 mg or 30 mg) plus SOC was assessed versus SOC only in patients with newly diagnosed/relapsing ANCA‐associated vasculitis. Efficacy measurements included 50% or greater reduction in Birmingham Vasculitis Activity Score (BVAS) at day 85, rapid reduction (day 29) of BVAS to a score of 0 that was sustained through day 85, change in Vasculitis Damage Index (VDI), renal response (improvement in estimated glomerular filtration rate [eGFR], hematuria, and albuminuria), and health‐related quality of life (HRQoL). Results: Forty‐two patients were randomized (n = 13 SOC, n = 13 avacopan 10 mg, and n = 16 avacopan 30 mg). Serious adverse events occurred in 15% and 17% of patients receiving SOC only and patients receiving avacopan with SOC, respectively. In the intent‐to‐treat population, BVAS response was high across arms (11 of 13 SOC, 11 of 12 avacopan 10 mg, and 12 of 15 avacopan 30 mg); increases in mean VDI were greater with SOC only than with avacopan plus SOC (0.3 versus 0.1). Avacopan 30 mg was numerically superior to placebo and avacopan 10 mg in early remission (15%, 8%, and 20% for SOC only, avacopan 10 mg, and avacopan 30 mg, respectively), improved eGFR (+2.0 ml/min/1.73m 2, +1.3 ml/min/1.73m 2, and +6.2 ml/min/1.73m 2, respectively), renal response (17%, 40%, and 63%, respectively), and measures of HRQoL. Conclusion: Avacopan in addition to SOC for ANCA‐associated vasculitis was well tolerated, and at the higher study dose, it appeared to improve time to remission (ClinicalTrials.gov identifier NCT02222155).